Using process tracing to evaluate unique events: The case of EXPO Milano 2015. (July 2017) - Busetti, Simone; Dente, Bruno
In the social sciences, there is an emerging interest in process tracing as a method for improving rigour and transparency in within-case inferences. Recently, the method has been proposed as a possible enhancement of theory-based approaches to evaluation, but applications of the method remain rare. In an attempt to fill this gap, process tracing was used to evaluate the Universal Exposition held in Milano in 2015 (EXPO2015). Mega-events of this kind are perfect candidates for 'testing' the method; although their effects have been widely discussed in the relevant literature, claims about the causal contribution of mega-events are not straightforward, and a number of ambiguities complicate any clear assessment of their consequences. Two in-depth case studies of projects related to EXPO2015 – the East External Highway and Refettorio Ambrosiano – demonstrate the advantages and feasibility of process tracing and of the application of Bayesian logic to evidence search, collection and assessment. In particular, case study results show that Bayesian scrutiny may reveal unexpected weakness in apparently obvious inferences and increase reliability in assessing less straightforward causal attributions.